Short-Term Meditation Training Fosters Mindfulness and Emotion Regulation: A Pilot Study - Fazia, Teresa; Bubbico, Francesco; Iliakis, Ioannis; Salvato, Gerardo; Berzuini, Giovanni; Bruno, Salvatore; Bernardinelli, Luisa (Frontiers in Psychology, 2020)
The practice of meditation has been historically linked to beneficial effects, not only in terms of spirituality but also in terms of well-being, general improvement of psychophysiological conditions and quality of life. The present study aims to assess the beneficial effects of a short-term intervention (a combination of 12 practical 1-hour sessions of meditation, called Integral Meditation, and lectures on neuroscience of meditation) on psychological indicators of well-being in subjects from general population. We used a one-group pretest-posttest quasi-experimental design, in which all participants (n=41, 17 men and 24 women, with a mean age of 41.1 years) underwent the same intervention. Out of these, 24 had already experienced meditation practice, but only 12 in a continuative way. Effects were assessed by the standardized Italian version of three self-report questionnaires: Core Outcome in Routine Evaluation-Outcome Measure (CORE-OM), Five-Facet Mindfulness Questionnaire (FFMQ) and Emotion Regulation Questionnaire (ERQ). The questionnaires were filled in at baseline and immediately after the last meditation session. Linear mixed effect models were used to evaluate pre-post treatment changes on each outcome. Participants showed a general, close to a statistically significant threshold, improvement in the total score of CORE-OM and its different domains. The total score of FFMQ (β=0.154, p=0.012) indicates a statistically significant increase in the level of mindfulness as well as in the domains acting with awareness (β=0.212, p=0.024), and non-judging of inner experiences (β=0.384, p<0.0001). Lastly, we observed a statistically significant improvement in the cognitive reappraisal ERQ domain (β=0.541, p=0.0003). Despite some limitations (i.e., small sample size, lack of a randomised control group and sole use of “soft” measurements, such as self-report questionnaires), this study offers promising results regarding the within-subject effectiveness of our intervention that includes a meditation practice on psychological indicators, thus providing interesting preliminary results.